Comparative Study of Satisfaction of BPJS Patients and Reguler Patients with Health Services at the Muara Tebo Community Health Center, Tebo Regency, Jambi: Studi Perbandingan Kepuasan Pasien BPJSdanPasien Umum Terhadap Pelayanan Kesehatan Di Puskesmas Muara Tebo Kabupaten Tebo Jambi - Mutia Puspa Rini; Saputra, Hermawan; Nurhayati, Tari (Jurnal Rekam Medis dan Informasi Kesehatan, 2024)
Patient satisfaction is a description of the extent to which the patient feels served in meeting the patient's health needs. Indicators of patient satisfaction include satisfaction with service access, service quality, service processes and service systems which affect all patients, both BPJS patients and general patients. This study aims to compare patient satisfaction at the Muara Tebo Community Health Center based on BPJS patients and general patients. This research is quantitative research with descriptive methods and a cross sectional approach. The population in this study is patients who visited in May-June 2023. The sample in this study used an accidental sample, namely determining the sample based on anyone who happened to meet the researcher and could be used as a sample according to the inclusion and exclusion method. The research results show that the Equal variances assumed value is known to be sig. (2 tailed) is 0.007 < 0.05, so as is the basis for decision making in the independent sample T-test, it can be concluded that H0 is rejected and Ha is accepted. There is a significant difference between the satisfaction of general patients and BPJS patients with health services at the Muara Tebo health center.